Mathematical modeling of intra- and inter-species interactions in mixed malaria within-host infections - Pane, Malick; Richard, Quentin; Seydi, Ousmane; Djidjou-Demasse, Ramsès (Journal of mathematical analysis and applications, 2025)
Malaria poses a significant global health challenge, with millions of cases and fatalities reported annually, primarily in the WHO African Region and South-East Asia Region. Mixed-species malaria infections are common but often underestimated, even in regions with low transmission rates. Mathematical models have been instrumental in studying parasite multiplication within hosts during mixed malaria infections, yet existing models typically focus on either intra-species or inter-species dynamics separately. However, both intra- and inter-species diversity are crucial in within-host malaria infection dynamics. In this study, we introduce a mathematical model for intra-species and inter-species interactions between P. vivax and P. falciparum, exploring their co-infection dynamics within hosts. We establish the properties of the model and conduct invasibility analysis in a multi-species and multi-genotypes framework. We also perform the uniform persistence of parasites over time within the host and discuss several typical scenarios that the model can simulate. Our findings shed light on the complex dynamics of malaria co-infections and their clinical implications.